PETA DAKWAH ISLAM DI KABUPATEN TAPANULI SELATAN - KAMALUDDIN KAMALUDDIN (IAIN Padangsidimpuan, 2017)
Nowadays people’s lives in region of South Tapanuli district, as well as in other regions are facing a number of challenges of dakwah; such as the influence og other religions, secularism, capitalism and liberalism, the negative impact if information and communication technology, and a variety of social deseases. Therefore, the conditionof the dakwah Islam with the problems and the solution needs to be mapped. Data were taken by using interviews and obsevation. Then, researchers found that the dakwah of Islam in this region has not run optimally, as expected. The Routine dakwah in the communities has not been found yet, except in several villages, and generally the dakwah just only happens on the anniversary of the great days, such as Isra’ Mi’raj or Maulid Nabi. It has found that the weakness of public interest to follow dakwah, and less of preacher with limited knowledge and skill. It is also found that the community chiristian from Nias tribe had inhabited as long as Bukit Barisan in Middle Tapanuli to South Tapanuli, and they opened their estatesand from their own community and built a church in the hills. This can lead to ethnic and religious conflict (SARA) when their harmony with the lecal population of Muslims ignored. Alternative solution that can be implemented is to establish coordination among preachers, Islamic organizations, MUI and Local Governments for impruving management of Dakwah Islam as well as increasing brotherhood and unity in the community